2013
DOI: 10.1371/journal.pone.0058792
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Structural Evidences on Human Prolidase Pathological Mutants Suggest Strategies for Enzyme Functional Rescue

Abstract: Prolidase is the only human enzyme responsible for the digestion of iminodipeptides containing proline or hydroxyproline at their C-terminal end, being a key player in extracellular matrix remodeling. Prolidase deficiency (PD) is an intractable loss of function disease, characterized by mutations in the prolidase gene. The exact causes of activity impairment in mutant prolidase are still unknown. We generated three recombinant prolidase forms, hRecProl-231delY, hRecProl-E412K and hRecProl-G448R, reproducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 50 publications
(61 reference statements)
1
35
0
Order By: Relevance
“…As a consequence of this, the nucleophilic attack would be facilitated. The proposed mechanism is also supported by kinetic analysis of the Glu412Lys mutant .…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of this, the nucleophilic attack would be facilitated. The proposed mechanism is also supported by kinetic analysis of the Glu412Lys mutant .…”
Section: Resultsmentioning
confidence: 99%
“…This change is accompanied by an increased active site flexibility and leads to a complete loss of enzyme activity. It is interesting to note for this variant, that in earlier modeling studies , this effect was not predicted. It is also surprising that biochemical studies on this variant mutant suggested the presence of both ions and hinted at slightly increased affinity .…”
Section: Discussionmentioning
confidence: 71%
“…It is interesting to note for this variant, that in earlier modeling studies , this effect was not predicted. It is also surprising that biochemical studies on this variant mutant suggested the presence of both ions and hinted at slightly increased affinity . This is clearly in contradiction to the results presented here.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Prolidase (PLD, EC 3.4.13.9) is a member of the matrix metalloproteinase family (5,6) . It is the only human enzyme responsible for the digestion of iminodipeptides containing proline or hydroxyproline at their C-terminal end, being a key player in collagen turnover, extracellular matrix remodeling and cell growth (5,(7)(8)(9) . Uzar et al (2012) stated that there is increased plasma prolidase enzyme activity in neuropathy due to diabetes (DN) as evidence of increased collagen turnover (10) .…”
Section: Introductionmentioning
confidence: 99%